2021
DOI: 10.3390/en14206581
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Impact of International Trade on Consumption-Based Carbon Emissions in MINT Nations

Abstract: The association between carbon emissions and international trade has been examined thoroughly; however, consumption-based carbon emissions, which is adjusted for international trade, have not been studied extensively. Therefore, the present study assesses the asymmetric impact of trade (import and export) and economic growth in consumption-based carbon emissions (CCO2) using the MINT nations (Mexico, Indonesia, Nigeria and Turkey) as a case study. We applied the Nonlinear ARDL to assess this connection using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 69 publications
(108 reference statements)
0
21
0
Order By: Relevance
“…Most countries around the globe rely significantly on non-renewable energy sources like coal, natural gases, and crude oil to satisfy the increasing energy need. The heavy dependence on fossil fuels has indeed intensified environmental problems (Adebayo et al, 2021a;Akinsola et al, 2021;Zhang et al, 2021). Anthropogenic greenhouse gas emissions (GHGs) have risen from the preindustrial period and are presently at their highest level.…”
Section: Introductionmentioning
confidence: 99%
“…Most countries around the globe rely significantly on non-renewable energy sources like coal, natural gases, and crude oil to satisfy the increasing energy need. The heavy dependence on fossil fuels has indeed intensified environmental problems (Adebayo et al, 2021a;Akinsola et al, 2021;Zhang et al, 2021). Anthropogenic greenhouse gas emissions (GHGs) have risen from the preindustrial period and are presently at their highest level.…”
Section: Introductionmentioning
confidence: 99%
“…It is anticipated that an increase in FD would decrease ED, i.e., β 5 = normalED normalFD <0. Following studies of Awosusi et al 58 and Mahmood et al, 59 UZN is incorporated into the model. UZN is anticipated to have a positive impact on ED, i.e., β 6 = normalED normalUZN >0.…”
Section: Methodsmentioning
confidence: 99%
“…The study found that income growth in these countries increases carbon emissions based on consumption. Additionally, Safi, Chen, et al (2021) analyzed the nexus between expansion in the economy and consumption‐based CO 2 E and concluded that in E‐7 countries, economic growth increases consumption‐based CO 2 E. According to Adebayo et al (2021), there is a correlation between growth and CO 2 E in Mexico, Indonesia, Nigeria, and Turkey (MINT) economies.…”
Section: Synopsis Of Related Literaturementioning
confidence: 99%